2012
DOI: 10.1093/ndt/gfs063
|View full text |Cite
|
Sign up to set email alerts
|

Population screening for chronic kidney disease: a survey involving 38 721 Brazilians

Abstract: This initiative provided information on proteinuria and possible cases of CKD based on a large sampling of the Brazilian population. Proteinuria was detected in 7.3% of these individuals, and such prevalence is similar to that previously described in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The semi-quantitative dipstick method of albuminuria assessment without confirmation test, the bias in reading the results and the presence of transient proteinuria could explain this high prevalence. Nevertheless, some authors have also reported low prevalence of albuminuria on dipstick with prevalence ranging from 2.25 to 7.4 %, which could reflect true lower risk of albuminuria in their population as well as bias in reading the results [ 10 , 11 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The semi-quantitative dipstick method of albuminuria assessment without confirmation test, the bias in reading the results and the presence of transient proteinuria could explain this high prevalence. Nevertheless, some authors have also reported low prevalence of albuminuria on dipstick with prevalence ranging from 2.25 to 7.4 %, which could reflect true lower risk of albuminuria in their population as well as bias in reading the results [ 10 , 11 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of Brazilian adults participating in CKD prevention campaigns (mean age 45±22 years), 7.3% of the 37,771 urine samples examined showed proteinuria. [ 3 ] The estimated prevalence of patients on chronic dialysis in Brazil in 2012 was 503 per million, with 31.9% aged ≥ 65 years. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…In Juiz de Fora (MG) the prevalence of CKD in individuals aged more than 18 years was 9.6% 9 , and in São Paulo (SP) the prevalence in adults was 8.4% 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies find higher prevalences of CKD, ranging from 15.3% in a community of ethnic minorities in China 32 to 21.8% in Iran 33 . Hence, the prevalence of CKD in the global population, especially in developing 28,30,33,35 . This difference between the prevalences can be explained by the fact that albuminuria increases gradually according to age and many studies did not include older adults.…”
Section: Discussionmentioning
confidence: 99%